OTHER-INITIATED INTERACTIONS THAT CONTRIBUTE TO RESILIENT OUTCOMES AMONG YOUNG ADULTS RAISED BY CAREGIVERS WHO MISUSE ALCOHOL - Mushonga, Simbai; van Breda, Adrian D. (International Journal of Child, Youth and Family Studies, 2024)
This study offers an understanding of interactional resilience processes between young adults raised by caregivers who misused alcohol and people in their social-ecology who initiated supportive interactions that enabled them to achieve better-than-expected outcomes. Multiple in-depth face-to-face interviews and a draw-and-write methodology were used with 15 National University of Lesotho undergraduate students raised by caregivers who misused alcohol. An interactional resilience approach, building on person-in-environment and social-ecology perspectives on resilience, informed this study. Using constructivist grounded theory methods of data analysis, three themes were formulated: (a) other-initiated material support that elicits a response of resolve or obligation towards the other; (b) other-initiated sustained emotional support that elicits a response of hope for the future; and (c) other-initiated challenging support that elicits a change in behaviour. Given these findings, the study recommends that child and youth workers and social workers cultivate enabling and support-initiating social environments in key contexts such as schools, churches, and clubs, and develop children and young people’s skills to respond to and receive such support.